Decreased bone mass in adolescents with bone fragility fracture but not in young children: a case–control study - Matkovic, Velimir; Goel, Prem; Mobley, Stacey L.; Badenhop-Stevens, Nancy E.; Ha, Eun-Jeong; Li, Bin; Skugor, Mario; Clairmont, Albert (Frontiers in Endocrinology, 2023)
Background: The incidence of distal forearm fracture due to minimal/moderate trauma shows a bimodal distribution for age at event, with one peak occurring during early adolescence, in both boys and girls and the other one in postmenopausal females. The aim of this study was, therefore, to document whether relationship between bone mineral density and fracture is different in young children compared to adolescents. Methods: A matched-pair, case-control study has been conducted to evaluate bone mineral density in 469 young children and 387 adolescents of both sexes, with/without fracture due to minimal/moderate trauma with assurance that the compared groups were equally susceptible to the outcome event. All fractures were radiographically confirmed. The study utilized bone mineral areal density of the total body, spine, hips, and forearm, volumetric bone mineral density of the forearm, and metacarpal radiogrammetry measurements. The study controlled for skeletal development, bone geometry, body composition, hand grip strength, calcium intake, and vitamin D status. Results: Adolescents with distal forearm fracture have reduced bone mineral density at multiple skeletal regions of interest. This was documented by the bone mineral areal density measurements at multiple skeletal sites (p<0.001), volumetric bone mineral density measurements of the forearm (p<0.0001), and metacarpal radiogrammetry (p<0.001). Adolescent females with fracture had reduced cross-sectional areas of the radius and metacarpals. Bone status of young female and male children with fracture was no different to its controls. Increased body fatness was more prevalent among fracture cases than in controls. About 72% of young female and male children with fracture had serum calcidiol [25(OH)D3] levels below the threshold of 31.4 ng/ml, compared to only 42% of female controls and to 51% of male controls. Conclusions: Adolescents with bone fragility fracture had reduced bone mineral density at multiple skeletal regions of interest, while this was not the case with younger children. The results of the study may have implications for the prevention of bone fragility in this segment of the pediatric population.